DAMPAK ARUS MODAL ASING TERHADAP TABUNGAN DOMESTIK DI INDONESIA - Suhardi Suhardi; M Faisal Akbar (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to estimate the effect of foreign capital inflows on domestic savings in Indonesia. This study uses secondary data obtained from various sources such as Economic and Monetary Statistics published by Bank Indonesia, Economics and Statistics published by the Central Statistics Agency, scientific journals, and other literature related to the topic of this research. The 5-year period from 2015-2019 uses a multiple linear regression model through the Eviews8 program. The estimation results show that foreign investment has a positive and insignificant effect on domestic savings in Indonesia. Gross domestic product has a positive and insignificant effect on domestic savings in Indonesia.